Influence of a lignification and mineralization of leaf tissues on resistance to a brown rust in common wheat plants - A. A. Konovalov; I. K. Shundrina; E. V. Karpova; I. V. Eltsov; E. A. Orlova; N. P. Goncharov (Вавиловский журнал генетики и селекции)
Aromatic substances in plant tissues can have protective effect against fungal diseases. One of the key enzymes in aromatic metabolism of plants, CAD (cinnamyl-alcohol dehydrogenase, dehydrogenase of cinnamyl alcohol; EC 1.1.1.195), at a number of species of plants exerts impact on the content of aromatic substances and on protective properties of tissues from fungal infections. When studying a collection of cultivars of bread wheat Triticum aestivum L., polymorphic on CAD, distinctions on extent of defeat are found by brown rust (with Puccinia recondita f. sp. Tritici as a causative agent). The purpose of the work was studying of features of structure and chemical composition of the tissues of a leaf promoting increased resistance. On a phytopathologic plot, against artificial infection with spores of a brown rust, two samples of spring bread wheat 3-13-15-4 and 3-4-14-3 were affected 1–5 % and 30 %, respectively. An analysis of various substances content in the leaf tissue at the contrast samples was conducted. Large plaques and spot consisting of mineral compounds were observed on the leaf surface of the more resistant plant. In ashes of leaves and ashes of a lignin differences in the maintenance of a number of mineral elements were also found. Lignin content on the dry mass of a leaf differed slightly (14.2 % vs 12.3 %), however there are differences in chemical composition. It is possible that the observed differences lead to afflict the plants with leaf rust to such different degrees. In that case these characteristics can be used for diagnostics of potential resistance of cultivars to fungal infection.